2016
DOI: 10.1016/j.jtcvs.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and management of chylothorax after Ivor Lewis esophagectomy for cancer of the esophagus

Abstract: Occurrence of chylothorax after prophylactic thoracic duct ligation during transthoracic esophagectomy for esophageal cancer is rare. In patients with high-output chylous fistula, an early rethoracotomy with repeat ligation of the thoracic duct is safe and helps to shorten recovery time. In cases of low-volume drainage, a conservative approach is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 36 publications
3
49
1
2
Order By: Relevance
“…Our results were similar to another retrospective report, in which a significantly higher incidence of vocal cord paralysis was associated with the McKeown MIE (11). For transthoracic esophagectomy, chylothorax is a well-known complication associated with high morbidity and mortality (12). A randomized controlled trial and a meta-analysis have reported that transthoracic esophagectomy is associated with a high incidence of pulmonary complications and chyle leakage and longer hospital stays (13,14).…”
Section: Discussionsupporting
confidence: 89%
“…Our results were similar to another retrospective report, in which a significantly higher incidence of vocal cord paralysis was associated with the McKeown MIE (11). For transthoracic esophagectomy, chylothorax is a well-known complication associated with high morbidity and mortality (12). A randomized controlled trial and a meta-analysis have reported that transthoracic esophagectomy is associated with a high incidence of pulmonary complications and chyle leakage and longer hospital stays (13,14).…”
Section: Discussionsupporting
confidence: 89%
“…In the modern era of upper gastrointestinal surgery, postoperative chylothorax is a dramatic complication that occurs between 1% and 9% of the time after esophagectomy for cancer . Although a rare event, chylothorax affects the postoperative morbidity by promoting the occurrence of pneumonia, with respiratory failure, malnutrition, and death in 20% of cases .…”
Section: Other Complications That May Influence the Conduit Or Anastomentioning
confidence: 99%
“…Postoperative chylothorax can be classified into three categories according to the daily output (volume/kg): low, medium, and high drain output . Brinkmann et al .…”
Section: Other Complications That May Influence the Conduit Or Anastomentioning
confidence: 99%
See 2 more Smart Citations